Reconstructing neuronal circuitry from parallel spike trains - Ryota Kobayashi (Nature Portfolio, 2019)
Current techniques have enabled the simultaneous collection of spike train data from large numbers of neurons. Here, the authors report a method to infer the underlying neural circuit connectivity diagram based on a generalized linear model applied to spike cross-correlations between neurons.